because (a + bi)*(a - bi) = a^2 -abi + abi -i^2b^2 = a^2 + b^2
Here, a and b are real, so a^2 + b^2 is not only real, but nonnegative.
2007-03-14 19:13:14
·
answer #1
·
answered by mitch w 2
·
1⤊
0⤋
The simple answer is that when they are multiplied the imaginary parts cancel out to zero leaving only the real part.
Example (3 +5i)(3 - 5i) = 9 + 15i - 15i -25i^2 = 9 + 25 = 34
2007-03-15 02:12:23
·
answer #2
·
answered by mathsmanretired 7
·
0⤊
0⤋
Let a + bi be the complex number. Its conjugate is a - bi. The product is as follows:
(a+bi)(a-bi) = a² - abi + bai - b²(i)²
The terms - abi and + bai cancel out, and (i)² becomes -1, so we're left with
a² + b², always a positive number.
2007-03-15 02:14:55
·
answer #3
·
answered by Scythian1950 7
·
2⤊
0⤋
The important property of complex numbers
is that i² = - 1.
Consider the product :-
(a + i b).(a - i b)
= a² - iab + iba - i²b²
= a² - iab + iab - (-1)b²
= a² + b² (a real number)
2007-03-15 03:42:08
·
answer #4
·
answered by Como 7
·
0⤊
0⤋
If z= a + ib, then the conjugate is a - ib, so
(a+ib)(a-ib) = a^2-(ib)^2 = a^2 - (-1)b^2 = a^2 + b^2
2007-03-15 02:17:40
·
answer #5
·
answered by blighmaster 3
·
0⤊
0⤋
see for yourself:
(x + a)(x - a) = x² + ax - ax - a² = x² - a²
the inner and outer products add to 0
(x + ai)(x - ai) = x² + axi - axi - a²i² = x² - a²i²
but i² = -1, so x² - a²i² = x² -a²(-1) = x² + a²
2007-03-15 02:17:38
·
answer #6
·
answered by Philo 7
·
0⤊
0⤋
because (a+bi)(a-bi)=a^2+b^2; a,b R
2007-03-15 02:14:12
·
answer #7
·
answered by djin 2
·
0⤊
0⤋